The Effect of Antigen Dose and Antigen Presenting Process on T Cell Stimulation: A Method for Enrichment of TB10.4 Antigen-specific T-cell Clones - Mahdieh Motiee; Ahmad Zavaran Hosseini; Sara Soudi; Seyed Mehdi Hassanzadeh (Iranian Journal of Allergy, Asthma and Immunology, 2021)
T-lymphocytes have critical functions in the immune responses against viral and intracellular bacterial infections as well as cancers. Antigen (Ag)-specific T-lymphocyte clones enriched and expanded in vitro are valuable tools in the study of immune responses in animal models and adoptive T-cell therapy of patients with cancer or infection. We described a method for inducing, enriching, and replicating Ag-specific poly-clonal T-cells from BALB/c mice infected with live Bacillus Calmette Guérin (BCG) bacterium. During a 7-8 days procedure, T-lymphocytes were purified from immune cells of lymph nodes stimulated with immunodominant Ag of BCG, TB10.4, and expanded by interleukin -2 cytokine. We evaluated the effect of Ag doses (1, 10, and 100 μg/mL) and exposure method of Ag presenting cells (APCs) to T-cells, on T-cells’ proliferation, viability, and Interferon-gamma (IFN-γ) secretion at 2, 5, and 7 days after Ag stimulation. Increasing Ag concentration increased the average cell division, but at the highest dose of Ag (100 μg/mL), T-cell viability is decreased. Only clones induced by 10 μg/mL Ag produced a desirable amount of IFN-γ. Incubation of Ag and APCs, 24 h before T-lymphocytes addition, increased the proliferation and viability of cells. T cells are in a more favorable condition around day 5 of Ag stimulation in terms of proliferation and survival, and it is the desired time for T cell restimulation. For optimal preparation of specific T-cells for adoptive cell transfer, optimization of Ag dose, the order of APCs and T-cells exposure with Ag, and the duration of initial Ag stimulation, as well as the time for restimulation, is essential.